Deeper into the dip - Kankondi, Sebbi Lenga Agarob (Rhodes University, 2026)
Given the increasing threat posed by climate change, particularly in environments marked by extreme temperature fluctuations and desiccation stress, understanding the adaptive strategies that underpin thermal tolerance is crucial for predicting species resilience. Central to this investigation is the concept of metabolic rate suppression (hypometabolism), an energy-saving mechanism widespread among animals exposed to stressful climatic conditions. This thesis investigates the ecophysiological responses of two pulmonate limpets, Siphonaria capensis and S. serrata, to the dynamic thermal conditions characteristic of South Africa’s rocky intertidal zones. An integrative approach was employed to address this objective. Field surveys, utilizing transect-quadrat analysis and capture–mark–recapture experiments, quantified microhabitat use and preference across sites spanning distinct biogeographic regions (West, South, and East coasts of South Africa). Complementing these field studies, a laboratory-based thermal preference assay using an artificial thermal gradient elucidated the role of behavioural thermoregulation, via thermotaxis, in the micro-scale distribution of S. capensis. In parallel, non-invasive plethysmography was used to derive key physiological indices, including final breakpoint temperature, flatline temperature, and a proxy for hypometabolism, cardiac suppression range, from species-specific cardiac responses to thermal stress. These parameters helped test the study’s primary hypotheses: that limpets inhabiting thermally stressful microhabitats, or those unable to escape such conditions, would exhibit more pronounced hypometabolic activity and consequently greater thermal limits than conspecifics in cooler environments. This premise originated from the assumption that hypometabolism extends functional thermal limits under heat stress. By integrating field observations, behavioural assays, and physiological measurements, this work contributes to a more nuanced understanding of how intertidal organisms mitigate thermal stress. Both species predominantly occupied, and exhibited pronounced preferences for, thermally benign microhabitats, such as crevices or coastal zones closer to the West coast. Neither species, however, exclusively avoided thermally suboptimal conditions. Furthermore, thermal history likely influenced these trends, with S. capensis demonstrating short-term thermal preferences linked to prior thermal acclimatization. This connection was corroborated by findings from the heart-rate analysis. Specifically, hypometabolism correlates with enhanced thermal tolerance, and through its transient and flexible nature, the consistency of this relationship is maintained across different thermal regimes. In summary, the study provides compelling evidence that hypometabolism extends the upper thermal limits of pulmonate limpets, and that the hypotheses rooted in metabolic rate suppression (MRS) theory are supported. I therefore conclude that MRS theory serves as a valuable framework for predicting species thermal resilience across diverse environmental conditions.
probing the ecophysiological implications of metabolic rate suppression in pulmonate limpets
Keywords: Intertidal ecology (http://id.loc.gov/authorities/subjects/sh85067534); Limpets (http://id.loc.gov/authorities/subjects/sh85077065); Dormancy (Biology) (http://id.loc.gov/authorities/subjects/sh85039101); Climatic changes (http://id.loc.gov/authorities/subjects/sh85027037); Intertidal animals--Effect of temperature on (http://id.loc.gov/authorities/subjects/sh85067535)